2018
DOI: 10.1177/0022022118795283
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Cyberbullying According to Ethnic-Cultural Origin in Adolescents: A National Study in Spain

Abstract: Studying the predictors of cyberbullying is of great research interest; however, little is known about how these relationships function in different ethno-cultural groups within a similar context. Our study examines levels of cyber victimization, cyber aggression, self-esteem, empathy, and social skills as possible predictors of cyberbullying in various ethno-cultural groups: Moroccan, Romanian, Colombian, Ecuadorian, and Spanish. A multicultural sample that was representative of students in their first throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 51 publications
(97 reference statements)
3
35
3
2
Order By: Relevance
“…A literature review showed that most of the studies about bullying and cyberbullying have been conducted in wealthy, Western countries [ 1 ]. Nevertheless, knowledge about violence, including associated risk and protective factors, is needed the most in disadvantaged areas, including many regions of Latin America [ 2 , 3 , 13 , 14 , 15 ]. This knowledge can only be gathered using validated measurement tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review showed that most of the studies about bullying and cyberbullying have been conducted in wealthy, Western countries [ 1 ]. Nevertheless, knowledge about violence, including associated risk and protective factors, is needed the most in disadvantaged areas, including many regions of Latin America [ 2 , 3 , 13 , 14 , 15 ]. This knowledge can only be gathered using validated measurement tools.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 10% of studies with a focus on different types of violence have been conducted in low- and middle-income countries, even though 85% of violent deaths occur in low- and middle-income countries [ 13 ]. The number of studies on bullying and cyberbullying in disadvantaged areas is also low [ 14 ] and, at the same time, understanding the subject is the key to reducing violence globally. For these reasons, it is necessary to validate instruments, to examine bullying and cyberbullying in disadvantaged regions, and to uncover possible risk and protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cyberbullying is an interpersonal, aggressive, repeated behavior whose purpose is harming a victim by means of information and communication technologies [9][10][11][12][13]. The cyberaggression that causes cybervictimization -the two dimensions of cyberbullying-is developed by means of cyberspace and other telematic channels, so it can be produced and reproduced in any place and at any time [7]. For cyberbullying to happen, it takes at least two people.…”
Section: Cyberbullyingmentioning
confidence: 99%
“…Nevertheless, three out of four of the studies on cyberbullying have been carried out in European countries or the USA [5]. This phenomenon has hardly been studied in countries of other more disadvantaged regions, such as the South American countries [6][7][8]. However, there is a small number of cross-cultural studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other signs the victims usually show are: reduced physical activity [10], decreased sleep duration [11], low self-esteem, difficulties in social skills [12], poor body image, poor eating habits [13], and consumption of alcoholic beverages [14]. More specifically, subjects who suffer cyberbullying tend to have mental health problems, engage in substance abuse, become overweight, and use video games for three or more hours a day [15].…”
Section: Introductionmentioning
confidence: 99%